Para além da flexibilização e precarização do trabalho : notas sobre a discussão do termo precarização do trabalho - Colombi, Bárbara Leite Pereira (2013)
This dissertation is linked to the line one in the master's degree of Social Policy at the Universidade Federal do Espírito Santo called "Reproduction and structure of contemporary capitalism." Its main objective is to analyze what it is the phenomenon of precarization of labor in the capitalist system. To achieve this we divide this work into three chapters: the first one sought to identify if historically the capitalist mode of production, in essence, left at some historical moment to introduce traits of insecurity. The second identified how the precariousness of work is used by authors, to contextualize the reader about the debate and finally there was an investigation if have similarity between the term precarious employment with the flexibility and intensification of work, in order to demonstrate the uniqueness of the term precarious work. The hypothesis of this research is the consideration that capitalism, in the way of story illustrates, imposed and imposing in its relations of classes, traces of fragility and precariousness for workers. This is the key point of this dissertation.